COMPARISON OF AESTHETIC SMILE PERCEPTIONS BETWEEN DENTISTRY AND ECONOMICS BUSINESS STUDENTS IN LAMBUNG MANGKURAT UNIVERSITY - Ratu Rini Alfikri; Diana Wibowo; Galuh Dwinta Sari (Dentino : Jurnal Kedokteran Gigi, 2023)
ABSTRACTBackground: Smile is one of the aesthetic components that contribute to person's attractiveness. The aesthetic smile is obtained from orthodontic treatment. The standard of orthodontic aesthetic smile is from the evaluation between smile arch and lower lip border, number of gaps, and amount of gingival, when smiling. Aesthetic concepts can be different because of perception. The difference in perception may be generated by a variety of variables. One of which is educational background. Purpose: This study aims to analyze the difference in perception of the aesthetic smile between dentistry students and economic business students at Lambung Mangkurat University. Method: This study used an analytic observational method with a cross-sectional approach. The sample was calculated using the Slovin formula and obtained 88 respondents who were taken using a simple random sampling technique. The questionnaire was measured on an ordinal scale using a visual analogue scale from 0-100. Before being distributed to respondents, the questionnaire was first tested for validity and reliability. Then, the results were analyzed using the Mann-Whitney test. Results: The significance of the Mann-Whitney test obtained a consonant smile of 0.000; a narrow buccal corridor of 0,000; a gingival display of a non-gummy smile of 0.006, and a symmetrical smile of 0.000. The four variables had a significance value of less than 0.05. It means that there was a difference between the two groups. Conclusion: There is a difference in perception of an aesthetic smile between dentistry students and economic business students at Lambung Mangkurat University. Keywords: Aesthetic Smile, College Student Perceptions, Smile Perceptions